Toward 3D structural information from quantitative electron exit wave analysis - Borisenko, K; Moldovan, G; Kirkland, A; Wang, A; Van Dyck, D; Chen, F (2012)
Simulations show that using a new direct imaging detector and accurate exit wave restoration algorithms allows nearly quantitative restoration of electron exit wave phase, which can be regarded as only qualitative for conventional indirect imaging cameras. This opens up a possibility of extracting accurate information on 3D atomic structure of the sample even from a single projection.